Diagnosis of hindlimb lameness using acupuncture points in sport horses - Tanakorn Phetkarl; Angkana Kidtiwong; Ashannut Isawirodom; Kritsana Watchararat; Kannika Na Lampang; Siriporn Khumsap; Porrakote Rungsri (Veterinary Integrative Sciences)
The detection of hindlimb lameness is usually considered to be more difficult than the forelimb lameness; thus, it tends to be overlooked. Therefore, an alternative diagnostic method employing acupuncture points for diagnosis of hindlimb lameness is being considered. The objective of this study was to identify the diagnostic acupoints associated with hock pain in sport horses with hindlimb lameness. In this study, 33 sport horses from polo and riding activities were examined for hock pain through acupuncture diagnosis (AD), subjective lameness examinations (SE) by experienced equine veterinarians’ opinions, and objective lameness examinations (OE) using body-mounted inertial sensor systems. From 33 horses, 14 horses with hock pain were included in this study and underwent intra-articular analgesia at the tarsometatarsal joint (TMT block). Each horse was then assessed and graded with the score of improvement for sensitivity of acupuncture points and lameness. From 14 horses, the results indicated that the kappa test for agreement of diagnostic method in determining lame limbs between AD and OE was 71.43% (95%CI = 51.33% - 86.77%), which was significantly higher when compared with the agreement between AD and SE at 64.29% (95%CI = 44.07% - 81.36%). Among the improved horses after TMT block, the score of improvement for sensitivity of acupuncture points also improved significantly on four transpositional acupoints. Based on our findings, Gallbladder-27, Spleen-13, Bladder-39a, and Bladder-39b were determined to be valuable suggestive acupoints for hock pain in horses with different sport activities. In conclusion, the results of this study advocate for the use of acupuncture diagnosis as a supporting lameness diagnosis method.